Terrorism the new world war - Pettiford, Lloyd (Acturus, 2003)
This book is about analysis of recent terror attacks, such as 9/11 and the Bali bomb attack. In addition, this books discusses in detail the most infamous acts of terror perpetrated, from kidnapping and murder of italian prime minister Aldo Moro, the US-Iranian hostage crisis of 1979.this books also is an attemp to explore the belief that problems rarely have easy answers and to show that terrorism today is a complicated anf threatening reality.